Screening prognostic genes related to leucovorin, fluorouracil, and irinotecan treatment sensitivity by performing co-expression network analysis for colon cancer - Wu, Pingping; Pan, Xuan; Lu, Kecen; Gu, Ning (Frontiers in Genetics, 2022)
Background: Colon cancer is one of the most common malignant tumors in the world. FOLFIRI (leucovorin, fluorouracil, and irinotecan) is a common combination chemotherapy regimen. However, insensitivity to FOLFIRI is an important factor in the effectiveness of treatment for advanced colon cancer. Our study aimed to explore precise molecular targets associated with chemotherapy response in colon cancer. Methods: Gene expression profiles of 21 patients with advanced colorectal cancer who received chemotherapy based on FOLFIRI were obtained from the Gene Expression Omnibus (GEO) database. The gene co-expression network was constructed by the weighted gene co-expression network analysis (WGCNA) and functional gene modules were screened out. Clinical phenotypic correlation analysis was used to identify key gene modules. Gene ontology and pathway enrichment analysis were used to screen enriched genes in key module. Protein-protein interaction (PPI) analysis was utilized to screen out key node genes. Based on the Gene Expression Profiling Interactive Analysis (GEPIA) database, the correlation between the expression levels of these genes and the overall survival (OS) and disease-free survival (DFS) of colon cancer patients was investigated, and the hub genes were screened out. Immunohistochemistry of candidate hub genes was identified using the Human Protein Atlas database. Finally, clinical information and RNA sequencing data of colon cancer were obtained from the Cancer Genome Atlas Project database (TCGA), GEPIA and the Human Atlas databases for validation. Results: WGCNA revealed that three hub genes were closely related to chemotherapy insensitivity of colon cancer: AEBP1, BGN and TAGLN. The protein expression levels of AEBP1, BGN and TAGLN in tumor tissues were higher than that in normal tissues. In addition, the gene expression levels of AEBP1, BGN and TAGLN were negatively correlated with OS and DFS in colon cancer patients. Therefore, AEBP1, BGN and TAGLN have been identified as potential biomarkers related to the response to FOLFIRI treatment of colon cancer. Conclusion: We found that AEBP1, BGN and TAGLN, as a potential predictive biomarker, may play an important role in the response to FOLFIRI treatment of colon cancer and as a precise molecular target associated with chemotherapy response in colon cancer.